What school leaders need to know about digital technologies and social media - McLeod, Scott, 1968-; Lehmann, Chris, 1971- (San Francisco, CA. : Jossey-Bass, 2012)
'Educational technology experts explain how to best integrate technology into K-12 schools, from blogs, wikis and podcasts to online learning, open-source courseware, and educational gaming to social networking, online mind-mapping, and using mobile phones'--
Includes bibliographical references and index.
Keywords: Educational technology -- Planning; Education -- Effect of technological innovations on; Social media; School management and organization